2016
DOI: 10.1111/pcmr.12480
|View full text |Cite
|
Sign up to set email alerts
|

FK506 positively regulates the migratory potential of melanocyte‐derived cells by enhancing syndecan‐2 expression

Abstract: Although topical tacrolimus (FK506) is known to promote repigmentation by increasing the pigmentation and migration of melanocytes, the mechanism through which FK506 regulates cell migration remains unclear. Here, we report that FK506 treatment enhanced cell spreading on laminin-332 and increased migration in both melanocytes and melanoma cells. Interestingly, FK506 also increased the expression of syndecan-2, a transmembrane heparan sulfate proteoglycan through c-jun terminal kinase activation. Moreover, siRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…67 In in vivo studies, TCI treatment led to a decrease in tumor necrosis factor and an increase in IL-10 in vitiligo lesions. 8,13 Second, TCIs induce the repigmentation of vitiligo by stimulating melanocyte proliferation and migration 14,15,[17][18][19] and melanin synthesis. 14,15,19,20 This process involves increasing MMP-2 and MMP-9 activity, 17 increasing endothelin B receptor expression in melanoblasts, 16 and promoting the secretion of stem cell factor from keratinocytes following TCI treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 In in vivo studies, TCI treatment led to a decrease in tumor necrosis factor and an increase in IL-10 in vitiligo lesions. 8,13 Second, TCIs induce the repigmentation of vitiligo by stimulating melanocyte proliferation and migration 14,15,[17][18][19] and melanin synthesis. 14,15,19,20 This process involves increasing MMP-2 and MMP-9 activity, 17 increasing endothelin B receptor expression in melanoblasts, 16 and promoting the secretion of stem cell factor from keratinocytes following TCI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8,[13][14][15][16][17][18][19][20][21][22] First, TCIs downregulate proinflammatory cytokines, such as tumor necrosis factor, 8 and induce antiinflammatory cytokines, such as interleukin (IL)-10, in the vitiligo lesions. 13 Second, calcineurin inhibitors promote the migration and proliferation of melanocytes and melanoblasts 15,18,19 through increasing matrix metalloproteinase (MMP-2 and MMP-9) levels 17 and inducing endothelin B receptor expression in melanoblasts. 16 In an in vitro study, proliferation of melanocytes was significantly enhanced by tacrolimus-treated keratinocyte supernatant.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Thus, SDC2 was elevated in tissue samples from both nevus and malignant human melanomas in contrast to the normal melanocytes, and its expression was correlated with enhanced migration . Additionally, SDC2 regulated a calcineurin inhibitor‐tacrolimus (FK506)‐mediated melanoma cell migration through FAK activation . Tacrolimus was found to induce melanocyte migration and melanogenesis and increase SDC2 expression through JNK signalling .…”
Section: Role Of Sdc2 In Cancermentioning
confidence: 97%
“…Additionally, SDC2 regulated a calcineurin inhibitor‐tacrolimus (FK506)‐mediated melanoma cell migration through FAK activation . Tacrolimus was found to induce melanocyte migration and melanogenesis and increase SDC2 expression through JNK signalling .…”
Section: Role Of Sdc2 In Cancermentioning
confidence: 99%
“…FK506’s effect on human melanocytes was further investigated, demonstrating that total melanin levels increased when stimulated with FK506. 56 , 57 Jung and Oh 57 also demonstrated that FK506 promotes melanocyte maturation, increases melanin content and tyrosinase levels within melanocytes, and enhances keratinocyte uptake of melanosomes. Jung and Oh 57 used sucrose fractionation and pH sensitive dyes to separate and evaluate melanosomes by maturity to evaluate these end points.…”
Section: Introductionmentioning
confidence: 95%